2008
DOI: 10.1007/s10532-008-9208-0
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic properties of a peroxidase-active cell-free extract from onion solid wastes: caffeic acid oxidation

Abstract: The exploitation of food residual sources consists of a major factor in reducing the polluting load of food industry wastes and developing novel added-value products. Plant food residues including trimmings and peels might contain a range of enzymes capable of transforming bio-organic molecules with potential phytotoxicity, including hydrolases, peroxidases and polyphenoloxidases. Although the use of bacterial and fungal enzymes has gained interest in studies pertaining to bioremediation applications, plant en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
11
2
1
Order By: Relevance
“…In the case of CGA, the molar ratio found was 1.6, which is higher than those reported for structurally similar hydroxycinnamate derivatives, including hydrocaffeic acid (El Agha et al 2008a) and CA (El Agha et al 2009), where the H 2 O 2 /substrate ratios determined were 1.33 and 0.8, respectively. However, this value is lower than that reported for FA, which was 2.56 (El Agha et al 2008b).…”
Section: Cga/h 2 O 2 Concentration Ratiocontrasting
confidence: 67%
See 1 more Smart Citation
“…In the case of CGA, the molar ratio found was 1.6, which is higher than those reported for structurally similar hydroxycinnamate derivatives, including hydrocaffeic acid (El Agha et al 2008a) and CA (El Agha et al 2009), where the H 2 O 2 /substrate ratios determined were 1.33 and 0.8, respectively. However, this value is lower than that reported for FA, which was 2.56 (El Agha et al 2008b).…”
Section: Cga/h 2 O 2 Concentration Ratiocontrasting
confidence: 67%
“…The ability of POD to form ferulic and caffeic acid (CA) dimers has been shown using an enzyme preparation from Bupleurum salicifolium callus cultures (Luis et al 2005), but more recently, the generation of FA (El Agha et al 2008a) and hydrocaffeic acid (El Agha et al 2008b) dimers, as well as CA tetramers (El Agha et al 2009), has been possible using a POD preparation from onion solid wastes.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen peroxide was utilized, once it promotes the activity of peroxidases (Agha et al 2009;Osborne et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Gc1. However, the increase in degradation in the presence of H 2 O 2 suggests the involvement of peroxidases (Agha et al 2009). Osborne et al (2006) reported that a chloroperoxidase from Caldariomyces fumago catalyzes H 2 O 2 -dependant dehalogenation reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Низкие константы скорости окисления фенотиазинов, возможно, как в случае с NADH и аскорбиновой кислотой, в первую очередь, обусловлены тем, что их окисление пероксидом водорода, протекает по одноэлектронному механизму, аналогично окислению неорганических субстратов пероксидазы [21,22]. Поэтому при совместном окислении ОДН и различных фенотиазинов, фермент реализует различные пути переноса электрона с окисляемого субстрата, выбор которых определяется доступностью функциональных групп субстрата каналам переноса электронов на поверхности белковой глобулы.…”
Section: фенотиазины -субстраты пероксидазы хренаunclassified